ADOPTION OF MASS MEDIA TECHNOLOGY ON INDUSTRY 4.0 PERSPECTIVE - Sri Oktika Amran; Muhammad David Hendra; Annisa Citra Triyandra; AB Sarca Putera; Ayu Adriyani (Jurnal Ranah Komunikasi, 2023)
Industry 4.0 has influenced the process of human communication from face-to-face to virtual. The communication process aligns with the Cyber-Physical System (CPS) concept. The CPS concept shows what is physically represented in cyberspace and vice versa. This has resulted in content production and distribution in the mass media adopting technological developments summarized in the CyberPhysical and Smart Factory systems. The adoption of technology that the mass media should carry out is a challenge for the sustainability of the media industry to carry out the function of the press. Thus, this article offers forms of technology adoption in the mass media using the literature review method in previous studies. The literature review results in this article offer technology adoption in the mass media from the perspective of industry 4.0. The form of technology adoption is the process of computational journalism as a production action based on Smart Factory. Furthermore, news automation is a production act and a CPS-based news distribution. This production and distribution process should involve the mass media workforce, which requires an approach to technology adoption by humans in the future mass media.